1995
DOI: 10.1016/0885-3924(95)00012-n
|View full text |Cite
|
Sign up to set email alerts
|

Anileridine-induced delirium

Abstract: Delirium is a common complication in hospitalized patients and is often associated with significant morbidity. It is important to recognize this syndrome early so that potential causes can be identified and properly managed. Although the etiology of delirium in critically or terminally ill patients is often multifactorial, opioid analgesics are often implicated as a potential underlying cause. Certain opioids, such as meperidine, have been identified as having a greater potential for causing delirium than othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Causes may include CNS involvement by the underlying pathology, terminal multiorgan failure, hyperhydration, hypercalcemia or drug side effect [21, 54,69]. Symptoms may worsen during the evening and night, or with sedating medication.…”
Section: Deliriummentioning
confidence: 99%
“…Causes may include CNS involvement by the underlying pathology, terminal multiorgan failure, hyperhydration, hypercalcemia or drug side effect [21, 54,69]. Symptoms may worsen during the evening and night, or with sedating medication.…”
Section: Deliriummentioning
confidence: 99%
“…Hallucinations have been previously described in patients requiring opioid analgesia (53)(54)(55)(56)(57)(58)(59)(60). Most of the reports have described visual hallucinations.…”
Section: Hallucinosis and Deliriummentioning
confidence: 99%
“…If the parent opioid or its active metabolites are suspected of being responsible for OIN, a rotation of the opioid may be instrumental in alleviating its effects. Several papers (summarized in Table 3) have shown this to be a safe and reliable method to decrease neurotoxicity but retain analgesia (58,60,76,79,81,(96)(97)(98)(99)(100)(101)(102)(103). Although the studies were uncontrolled and the total number of patients was small, all patients in these studies had evidence of OIN and all were observed to have significant improvement following the rotation of the opioid.…”
Section: Opioid Rotationmentioning
confidence: 99%